Pengaruh Harga Tiket dan Kualitas Layanan terhadap Keputusan Berkunjung ke Taman Bunga Nusantara - Indrianti Indrianti; Deri Apriadi (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This study aims to analyze the influence of ticket prices and service quality on the decision to visit Taman Bunga Nusantara. This study uses a quantitative approach with a survey method, which was conducted on 51 respondents who had visited the destination. The sampling technique used accidental sampling, and the data was analyzed using multiple linear regression. The results of the study showed that partially, ticket prices did not have a significant effect on the decision to visit, with a significance value of 0.719 (> 0.05). On the other hand, service quality had a significant effect on the decision to visit, with a significance value of <0.001. Simultaneously, the variables ticket price and service quality had a significant effect on the decision to visit, with a significance value of 0.000 and Fcount of 30.048. These results indicate that service quality has a more dominant influence than ticket prices in forming the decision to visit Taman Bunga Nusantara.